PENGARUH KEPEMIMPINAN, BUDAYA ORGANISASI DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR KECAMATAN EREMERASA KABUPATEN BANTAENG - Hidayati, Andi (Indonesian Journal Of Law Studies, 2024)
Thepurposeofthis researchare: 1)Todeterminetheinfluence ofleadershipon employeeperformance attheEremerasa Sub-District, Bantaeng  Regency,  2)  To  determine  the  influence  of  organizational culture   on   employee   performance   at   the   Eremerasa   Sub-District, BantaengRegency,3)To determinetheinfluenceofworkdisciplineon employeeperformanceatthe Eremerasa Sub-DistrictOffice, Bantaeng Regency, 4)To determinethesimultaneous influenceof leadership, organizational culture,andworkdisciplineon employeeperformance at theEremerasa Sub-District,Bantaeng Regency, 5)Toidentifywhich variable  has  a  greater  influence  among  leadership,  organizational culture, and workdisciplineon employeeperformance attheEremerasa Sub-District,BantaengRegency.The research methodemployedinthis studyis asurveymethod with aquantitativeapproach, focusingon hypothesis testing.The populationconsists of 40individuals, andthe sampleisdrawnusingacensusmethod,resulting inasamplesizeof40 respondents.Datais collectedthroughquestionnairesanddirect observation.Thedata analysisiscarriedoutdescriptivelyusing quantitativemethodswiththe SPSSprogram,utilizingmultiplelinear regressionanalysis.The researchfindingsindicatethatleadership, organizationalculture, andworkdisciplinecollectivelyhavean 84% influenceonemployee performanceattheEremerasaSub-District, Bantaeng  Regency,  while  the  remaining  16%  is  explained  by  otherEdy,  Sutrisno.  (2004).  Manajemen  Sumber  Daya  Manusia.  Jakarta:  KencanaPrenadaMediaGroup. E.Mulyasa.(2002).ManajemenBerbasisSekolah.Bandung:Rosdakarya. Greendberg,  Jerald,  Robert  A.Barron,  2005.  Behavior  inOrganization,  Fourth  Edition, AllynandBacon,USA Hartati(2016).“PengaruhMotivasiKerja,DisiplinKerja,danKompetensi terhadapKinerja Pegawaipada DinasPengelolaanSumberDaya Air,PertambangandanEnergi KabupatenSoppeng”.Tesis.Makassar:PascasarjanaSTIEAMKOP.Hadari,Nawawi.(2006).Kepemimpinan  Mengefektifkan  Organisasi.Yogyakarta:GadjahMadaUniversityPress. HamzahB.UnodanNinaLamatenggo.(2012).TeoriKinerjadanPengukurannya. Jakarta:BumiAksara.Hasibuan,  Malayu,  S.P.  (2009).  Manajemen  Sumber  Daya  Manusia.  Jakarta:GunungAgung.IvancevichJohnM,2002,PerilakudanManajemenOrganisasi,ed7,Erlangga,Jakarta. Ichlapio  Fitrianto  (2016),  “Pengaruh  motivasi,  disiplin,  dan  kepuasan  kerja,  terhadapkinerjakaryawanPT.BumiRamaNusantara”.  Tesis.Makassar:  Pascasarjana  STIE AMKOPKartini,  Kartono.  (2008).  Pemimpin  danKepemimpinan  Apakah  KepemimpinanAbnormalitu?.Jakarta:RajaGrafindoPersada. Makkira  (2016  “Pengaruh  disiplin  kerja,  komitmen  organisasi,  dan  lingkungan  kerjaterhadap  kinerja  karyawan  pada  PT.  Trans  retail  indonesia  (carrefour)  cabang35                                                                                                       AndiHidayati,Vol.2 No.1 Juli2023  Mangkunegara,  A.A.AnwarPrabu.(2001).  Manajemen  SumberDayaManusiaPerusahaan.Bandung:RemajaRosdakarya. Mendikna